Human kidney is a target for novel severe acute respiratory syndrome coronavirus 2 infection - Bo Diao (Nature Portfolio, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can lead to acute kidney injury. The authors describe that SARS-COV-2 can directly infect human kidney, possibly mediating tubular pathogenesis.